Covered Stent of the Left Common Carotid and Subclavian Arteries Assist the Invasive Tumor Resection. (8th December 2020) - Tsukamoto, Yo; Nakada, Takeo; Fukushima, Soichiro; Yabe, Mitsuo; Toya, Naoki; Akiba, Tadashi; Ohtsuka, Takashi; Ohki, Takao
Abstract : Background . Some recent reports have described the usefulness of thoracic aortic stent grafts to facilitate en bloc resection of tumors invading the aortic wall. We report on malignant peripheral nerve sheath tumor resection in the left superior mediastinum of a 16-year-old man with neurofibromatosis type 1. The pathological margin was positive at the time of the first tumor resection, and radiation therapy was added to the same site. After that, a local recurrence occurred. The tumor was in wide contact with the left common carotid and subclavian arteries and was suspected of infiltration. After stent graft placement of these arteries to avoid fatal bleeding and cerebral ischemia by clamping these arteries and bypass procedure, we successfully resected the tumor without any complications. Conclusion s. Here, we report the usefulness of the prior covered stent placement to aortic branch vessels for the resection of invasive tumor.